Racial/Ethnic Differences in the Use of Complementary and Alternative Medicine in US Adults With Moderate Mental Distress - Taeho Greg Rhee; Roni L. Evans; Donna D. McAlpine; Pamela Jo Johnson (SAGE Publishing, 2017)
Objectives: To examine the prevalence of complementary and alternative medicine (CAM) use by race/ethnicity and to identify sociodemographic and health-related factors associated with CAM use among US adults with moderate mental distress (MMD). Methods: We analyzed data from the 2012 National Health Interview Survey (NHIS). We used data for 6016 noninstitutionalized US adults with MMD (3492 non-Hispanic whites, 953 non-Hispanic blacks, 1078 Hispanics, 268 Asians, and 225 others consisted of American Indian, Alaska Native, and those reporting multiple races). The 2012 NHIS asks about 36 types of CAM use in the past 12 months. We constructed (1) overall, any CAM use; (2) 5 major types of CAM use; and (3) individual types of CAM use indicators. Using a cross-sectional design with complex survey techniques, we estimated race/ethnicity-specific CAM prevalence, and odds of past year CAM use by race/ethnicity, sociodemographic, and health-related factors. Results: Nearly 40% of adults with MMD used CAM in the past year compared with 32% of those without MMD ( P < .001). In adults with MMD, past year CAM use differed by race/ethnicity, ranging from 24.3% (blacks) to 44.7% (Asians) and 46.8% (others) ( P < .001). Being younger, female, living in the west, higher education, being employed, more than 4 ambulatory care visits, and functional limitations were associated with higher odds of CAM use ( P < .01). Conclusions: Adults with MMD use CAM more frequently than those without MMD. In addition, CAM use was significantly differed by race/ethnicity in adults with MMD. This underscores the need for good patient-provider communication and suggests opportunity for dialogue about integration between conventional providers and CAM practitioners to facilitate optimal mental health care.